Introducing research methodology : a beginner's guide to doing a research project - Flick, Uwe, 1956- (Los Angeles : SAGE, 2015)
In the Second Edition of this textbook designed for new researchers, Uwe Flick takes readers through the process of producing a research project. The book gives readers the fundamental data collection and analysis skills that they need for their first project, as well as a good understanding of the research process as a whole. It covers both quantitative and qualitative methods, and contains plenty of real-life examples from the author's own research. The book will help readers to answer questions such as: Why do social research in the first place? How do I develop a researchable question? What is a literature review and how do I conduct one? How could I collect and analyze data? What if I want to do my research online?
Part I: Orientation -- Why social research? -- Worldviews in social research -- Ethical issues in social research -- From research idea to research question -- Part II: Planning and design -- Reading and reviewing the literature -- Planning social research : steps in the research process -- Designing social research -- Deciding on your methods -- Part III: Working with data -- Collecting quantitative and qualitative data -- Analyzing quantitative and qualitative data -- E-research : doing social research online -- Triangulation and mixed methods -- Part IV: Reflection and writing -- What is good research? Evaluating your research project -- Writing up research and using results.
Includes bibliographical references (pages 273-284) , glossary, and indexes.
Keywords: Social sciences -- Research; Research -- Methodology; Social sciences -- Research -- Methodology; Samhällsvetenskaplig forskning -- metodik